PENGARUH NET PROFIT MARGIN (NPM), RETURN ON ASSET (ROA) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR KOSMETIK DAN KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BEI - Sri Intan Purnama; Heni Ahmayani; Susana Dewi; Wahyu Hari Prihantono; Herlina (Universitas La Tansa Mashiro, 2025)
This study aims to prove whether there is a significant influence of Net Profit Margin (NPM), Return on Assets (ROA), and Earning Per Share on Stock Prices both partially and simultaneously in Cosmetics and Household Needs sub-sector companies for the period 2010-2024. The data in this study uses secondary data in the form of financial reports obtained through the Indonesia Stock Exchange website www.idx.co.id, with a sampling technique using purposive sampling resulting in a sample of 82 cosmetics and household needs sub-sector companies. The analytical tool used in this study is Eviews 12, the data prerequisite test uses the classical assumption test consisting of the normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, while the data analysis technique uses panel data regression analysis, partial test, simultaneous F test, correlation test and coefficient of determination test. The results of the study show that Net Profit Margin and Return on Assets have a significant effect on Stock Prices, partially. While Earning Per Share does not have a significant effect on Stock Prices partially. Meanwhile, simultaneously, Net Profit Margin (NPM), Return on Assets (ROA) and Earning Per Share (EPS) have a significant effect on stock prices..